Effective Utilization of Shared Nearest Node for Message Diffusion in Social Network Using Dbscan - Apoorva, P.; Akshay, S.; Priyanka, R.; Nayana, N. (International Journal of Engineering and Technology, 2018)
The social networking service has been enormously used among various people to share information or to build social relationship between acquaintances and other people as well. This term is used to describe a social structure where many users can bring forth their perspective on certain global information or imbalances that has been occurred over centuries.Â  The goal of Information diffusion is to spread messages over a network with a lesser time complexity and efficient accessibility. Here, to ease the process of message diffusion in social networking, we are finding overlapping nodes between commonly Shared Nearest nodes and aid in spreading the information more appropriately by reducing the complexity in the existing system and promoting an efficient level of performance. Density-based clustering is a relevant method we have used to trace shared nearest neighbor node. Also, we provide security for the data that is being diffused by implementing the RSA security algorithm and providing the security key along with the information and hence the group of people who are eligible to access the data with the security key can only access the data. Hence the information is being diffused evenly to each part in the cluster with less time complexity and efficiency.Â Â